Sulphite oxidase as key enzyme for protecting plants against sulphur dioxide - LANG, CHRISTINA; POPKO, JENNIFER; WIRTZ, MARKUS; HELL, RÜDIGER; HERSCHBACH, CORNELIA; KREUZWIESER, JÜRGEN; RENNENBERG, HEINZ; MENDEL, RALF R; HÄNSCH, ROBERT (Plant, Cell & Environment, 2007)
Sulphur dioxide (SO2) is known as a strongly damaging air pollutant. After conversion to sulphite in aqueous solution, it becomes a strong nucleophilic agent that attacks numerous compounds in the cell. Therefore, plants have developed a mechanism to control sulphite levels. Recently, we have cloned and characterized the enzyme sulphite oxidase (SO) from Arabidopsis thaliana. Yet, its physiological role remained unclear. Here, we describe results demonstrating that SO is essential for detoxifying excessive amounts of sulphite in the cell which is important for the survival of the plant. T-DNA-tagged A. thaliana plants lacking the enzyme showed a decrease in vitality during SO2 fumigation and a change in their S-metabolites. The same was found with RNA-interference (RNAi) plants that were generated for tobacco. On the contrary, over-expression of SO helped the plant to survive SO2 concentrations that are detrimental for non-transformed wild-type (WT) plants, as was shown with poplar plants which are known to be particularly sensitive to SO2. Fumigation induced the expression of the enzyme as demonstrated by promoter–reporter gene fusion, by immunoblot analysis of SO-protein and by induction of enzyme activity. This implies that SO, as an otherwise constitutively expressed protein, is under additional control by SO2 in the environment.
Keywords: acid rain; SO2 gas

Elevated atmospheric CO2 causes seasonal changes in carbonyl emissions from Quercus ilex - KREUZWIESER, JÜRGEN; Cojocariu, Cristian; Jüssen, Vera; RENNENBERG, HEINZ (New Phytologist, 2002)
* • The effect of elevated atmospheric CO2 on the carbonyl emissions of leaves from two Mediterranean oak species (Quercus ilex and Q. pubescens) was analyzed under field conditions. * • Physiological and meteorological parameters were determined in parallel with measurements of carbonyl emissions. Gas exchange was quantified in dynamic cuvettes combined with an infrared gas analyzer. * • Acetaldehyde and acetone emissions from leaves of Q. ilex were enhanced by elevated CO2 in the autumn (from 14–40 nmol m−2 min−1 and from 2–8 nmol m−2 min−1, respectively), but not in the summer. No significant effects were found for leaves of Q. pubescens. The effects of CO2 on Q. ilex were mainly a result of decreased emissions by control trees under ambient CO2 concentrations in the autumn; emissions from trees exposed to elevated CO2 remained at a high level. * • Elevated atmospheric CO2 causes autumnal changes in carbonyl emissions from Quercus ilex. These effects suggest that the production of acetaldehyde and acetone depend on developmental factors. It is not yet clear whether the altered carbonyl emissions are a unique feature of Q. ilex.
Keywords: Acetaldehyde; carbonyl emission; Elevated CO2; Quercus ilex; Quercus pubescens; VOC